The Technical Analyse of Violoncello Etudes - Gorgoretti, Basak (Ani Yayincilik, 2013)
Problem Statement: Cultivating the capacity for strong technique and vivid expression within each student is widely accepted as the primary goal in violoncello education. In this context etudes play an important role for the development of technical and musical aspects. Within the research literature the musical dimensions of etudes in violoncello albums are analysed from different perspectives such as tonality, speed terms, rhythmic structures, compositional styles, and technical difficulties. This study investigates the etude books used most often within Music Education departments of Turkish universities. The study also analyses the technical subjects of the two most used etude books. Purpose of the Study: This study aims to present the etude books used most often within Music Education departments of Turkish universities. The study further intends to analyse those etudes in terms of technical subjects and presents creative practices to be used in their preparation. Method: 'Document Analysis' method is used in the study. In order to determine the most used etude books, the universities in Turkey within Music Education Departments have been selected as a study group. Interviews were done with 23 cello instructors from 18 universities. J.J.F. Dotzauer's 113 Etudes for Violoncello, Book I and S. Lee's Melodische und Progressive Etuden are used most often. Technical subjects regarding to left and right hand use are analysed in both etude albums. Besides the most commonly used techniques within both etude albums are discovered. Findings and Results: Results of these interviews showed that the most often used etude books are Dotzauer's 113 Etudes for Violoncello, Book I and Lee's Melodische und Progressive Etuden Fur Violoncello, Op.31. All etudes included in both books are analysed to obtain the shared technical subjects of left and right hand use. Eight technical subjects of left hand use shared between the two etude books: keeping the fingers in position, double stops, arpeggios, articulation, trill, left hand agility, position establishment and left and right hand coordination. Five technical subjects of right hand use shared between the two etude books: string crossings, staccato, legato, detache and balancing the speed of the bow. In the second part of findings creative technical practices for common technical subjects within the two etude books are written. Conclusions and Recommendations: A comparison between the etude albums is presented. Implications for violoncello education are discussed.
Keywords: Etude; technical subject; technical practice; Dotzauer; Lee